MEK1/2 Inhibitor (GDC0623) Promotes Osteogenic Differentiation of Primary Osteoblasts Inhibited by IL-1β through the MEK-Erk1/2 and Jak/Stat3 Pathways - Zeng-Qiao Zhang; Xiao-Shen Hu; Ye-Chen Lu; Jun-Peng Zhang; Wen-Yao Li; Wei-Yang Zhang; Wei Feng; Dao-Fang Ding; Jian-Guang Xu (International Journal of Endocrinology)
Objective. We evaluated the effects and mechanisms of GDC0623 on osteogenic differentiation of osteoblasts induced by IL-1β. Methodology. Osteoblasts were treated with 20 ng/ml IL-1β and 0.1 µM GDC0623. Cell proliferation levels were evaluated by the cell counting kit 8 (CCK8), EdU assay, and western blotting [proliferating cell nuclear antigen (PCNA) and Cyclin D1]. Osteoblasts were cultured in an osteogenic induction medium for 1–3 weeks after which their differentiations were assessed by alkaline phosphatase (ALP) staining, Alizarin Red staining, calcium concentration, immunocytochemistry staining, real-time quantitative PCR (RT-qPCR), and immunofluorescence staining. The osteogenesis-associated mechanisms were further evaluated by western blotting using appropriate antibodies. Results. Relative to the control group, IL-1β induced the rapid proliferation of osteoblasts and suppressed their osteogenic differentiations by upregulating the activities of MEK-Erk1/2 as well as Jak-Stat3 pathways and by elevating MMP13 and MMP9 levels. However, blocking of the MEK-Erk1/2 signaling pathway by GDC0623 treatment reversed these effects. Conclusion. Inhibition of Jak-Stat3 pathway by C188-9 downregulated the expression levels of MMP9 and MMP13, activated MEK-Erk1/2 pathway, and inhibited osteogenic differentiation.